Pengaruh Social Marketing Terhadap Keputusan Berdonasi Yang Di Mediasi Oleh Kepercayaan Donatur Pada Badan Amil Zakat Nasional Provinsi Kalimantan Selatan - Marhusin, Marhusin; Taharuddin, Taharuddin (JURNAL BISNIS DAN PEMBANGUNAN, 2023)
The aim of this study is to examine and analyze the direct and indirect influence of  Social Marketing on Donation Decisions mediated by the Donor Trust at the National Amil Zakat Agency of South Kalimantan Province. The research location is at the National Amil Zakat Agency of South Kalimantan Province (Baznas Kal-Sel). The research sample of 100 respondents who were randomly selected (random sample sampling) with the characteristics of respondents is the Baznas Kal-Sel muzakki who is active in 2023 and lives in South Kalimantan. Questionnaires are used for data collection and data processing to test hypotheses and SEM-PLS to analyze the data. The results of the study prove that Social marketing has a significant effect on the decision to donate, Social marketing has a significant effect on donor trust, Donor trust has a significant effect on the decision to donate. Social marketing has a significant indirect effect on donation decisions mediated by donor trust. Keywords: Social Marketing, Donor Trust, Donation Decision